Lithium speciation in the LiPF6/PC electrolyte studied by two dimensional heteronuclear overhauser enhancement and pulse field gradient diffusometry NMR - Kumar, Vikas; Reddy, R. Ravikanth; Kumar, B. V. N. Phani; Avadhani, Chilukuri V.; Ganapathy, Subramanian; Chandrakumar, Narayanan; Sivaram, Swaminathan (Journal of Physical Chemistry C, 2019)
Electrolytic dissociation of lithium hexafluorophosphate (LiPF6) in the nonaqueous cyclic propylene carbonate (PC) has been investigated in the wide range of concentration (0.05-3.5 M) by Li-7 solution-state nuclear magnetic resonance (NMR) spectroscopy. Two-dimensional heteronuclear Overhauser enhancement spectroscopy NMR experiments have not only enabled the cation solvation and ion-pairing to be directly monitored but additionally evidence anion solvent interaction at higher concentrations (>1.2 M) of the PC electrolyte. Preliminary analysis of kinetic nOe data has been made to determine site-dependent cross-relaxation rates for the spatial interaction of the solvent with the Li+ cation and the PF6- anion. The concentration dependence of the Li-7 NMR self-diffusion coefficient (D-self), determined using very strong pulsed magnetic field gradients (similar to 1700 Gauss/cm), depicts two breaks to mark the solvation and ion-pairing events in a distinct manner. This in turn has aided the determination of solvent coordination number and average sizes of solvated and ion-paired clusters. Our results indicate that in the contact ion pair (CIP)-dominated electrolyte (>2 M), lithium-ion mobility across the solvated and ion-paired environments appears to be inhibited which makes the spectral distinction of solvated and ion-paired environments possible. The concentration dependence of the Li-7 NMR spectral and diffusometry data is in striking correspondence with that of bulk conductivity measurements and point to the detrimental effect of CIP aggregates in impeding the ionic conductivity at high salt concentrations. These results have significance in understanding the structure and dynamics of lithium-ion solvates that are ubiquitous in the working environment of a lithium-ion battery.